1990
DOI: 10.1055/s-2007-1014525
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Neuroleptic and Antidepressant Overdose: Epidemiological, Electrocardiographic, and Clinical Features* - A Survey of 92 Cases

Abstract: From 1976 to 1980, there were 3,193 admissions due to acute drug overdosage at the resuscitation centre of the Rudolf-Virchow-Hospital, Free University of Berlin. The frequency and the characteristics of selfpoisoning with antidepressants and low-potency neuroleptic drugs (mainly perazine and thioridazine) were determined. These drugs were involved in 92 cases (3%) during this five-year period. Amitriptyline--in combination with a benzodiazepine--was the most common antidepressant taken by the patients. Ten of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…A review of hospitalizations for TCA overdose by Kresse-Hermsdorf and colleagues found the most common adverse effect of a TCA overdose was having a prolonged QT interval. 18…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of hospitalizations for TCA overdose by Kresse-Hermsdorf and colleagues found the most common adverse effect of a TCA overdose was having a prolonged QT interval. 18…”
Section: Resultsmentioning
confidence: 99%
“…9 The impact of these agents on the QTc interval is well documented. [11][12][13][14][15][16][17][18][19] The effects of specific agents will be discussed below, and a summary of effects on the QTc interval can be found in Table 2. A self-controlled crossover study conducted by Iribarren and colleagues investigated the effects of drugs known to impact the QT interval.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies mag -analog zu den TCA -an ihrer arrhythmogenen [17] und epileptogenen Wirkung liegen. Thioridazin ist eine besondere Kardiotoxizität nachgesagt worden [5].…”
Section: Zu Den Neuroleptikaunclassified